2020
DOI: 10.3892/mmr.2020.11626
|View full text |Cite
|
Sign up to set email alerts
|

Sustained activation of C3aR in a human podocyte line impairs the morphological maturation of the cells

Abstract: The c3a receptor (c3ar) has been reported to be involved in various physiological and pathological processes, including the regulation of cellular structure development. expression of c3ar has been reported in podocytes; however, data concerning the role of c3ar in podocyte morphology is scarce. The aim of the present study was to examine the effect of c3ar activation on the architectural development of podocytes. an immortal human podocyte line (HPc) was transfected with a c3a expression lentivirus vector or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…In the alternative pathways, C3a and C5a can anchor to relative receptor, named as C3aR, and further activate the downstream pathways. Except the crucial roles in the complement system, C3aR also involved into other biological processes, for example as an immune checkpoint receptor in cancer immunotherapy 12 , leading the neurodevelopmental damage [13][14] , participating in white matter injury after hyperperfusion [15][16] . For proliferation of cancer cells, Chen B et al demonstrated that down-regulation of C3aR can inhibit the cell proliferation in hepatocellular carcinoma affecting the expression levels of extracellular matrix [17][18] ; over-activation of complement C3 can lead PD-L1 treatment resistance by modulating in ltration levels of tumor-associated macrophages through regulating the C3a-C3aR-PI3Kgamma signaling pathway 18 ; Mueller-Ortiz SL et al revealed that overexpression of C3aR can provides the host protection against listeria monocytogenes-induced apoptosis 19 ; Nabizadeh JA et al…”
Section: Introductionmentioning
confidence: 99%
“…In the alternative pathways, C3a and C5a can anchor to relative receptor, named as C3aR, and further activate the downstream pathways. Except the crucial roles in the complement system, C3aR also involved into other biological processes, for example as an immune checkpoint receptor in cancer immunotherapy 12 , leading the neurodevelopmental damage [13][14] , participating in white matter injury after hyperperfusion [15][16] . For proliferation of cancer cells, Chen B et al demonstrated that down-regulation of C3aR can inhibit the cell proliferation in hepatocellular carcinoma affecting the expression levels of extracellular matrix [17][18] ; over-activation of complement C3 can lead PD-L1 treatment resistance by modulating in ltration levels of tumor-associated macrophages through regulating the C3a-C3aR-PI3Kgamma signaling pathway 18 ; Mueller-Ortiz SL et al revealed that overexpression of C3aR can provides the host protection against listeria monocytogenes-induced apoptosis 19 ; Nabizadeh JA et al…”
Section: Introductionmentioning
confidence: 99%